2014
DOI: 10.1073/pnas.1400997111
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic control of selective neural activity in multiple freely moving Drosophila adults

Abstract: We present an automated laser tracking and optogenetic manipulation system (ALTOMS) for studying social memory in fruit flies (Drosophila melanogaster). ALTOMS comprises an intelligent central control module for high-speed fly behavior analysis and feedback laser scanning (∼40 frames per second) for targeting two lasers (a 473-nm blue laser and a 593.5-nm yellow laser) independently on any specified body parts of two freely moving Drosophila adults. By using ALTOMS to monitor and compute the locations, orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…From these exciting results, we realize that non-invasive, versatile, economical behavioral machines will help scientists screen behavior-related neuron circuits. In the present work, we improved our previous automated laser tracking and optogenetic manipulation system (ALTOMS) [10]. First, we found that ventral irradiation requires reduced laser intensity compared to dorsal irradiation.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…From these exciting results, we realize that non-invasive, versatile, economical behavioral machines will help scientists screen behavior-related neuron circuits. In the present work, we improved our previous automated laser tracking and optogenetic manipulation system (ALTOMS) [10]. First, we found that ventral irradiation requires reduced laser intensity compared to dorsal irradiation.…”
Section: Introductionmentioning
confidence: 82%
“…In ventral irradiation ALTOMS, we attempted to use an economical long-pass filter (Thorlab FGL610, 610 nm long-pass color filter) to replace the two notch filters (Kaiser HNF-473.0, HNF-593.5) used in the first-generation ALTOMS [10]. Figure 2(D) displays the image of the CCD camera with the notch filters.…”
Section: System Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, channelrhodopsin-2 (ChR2) is a light-gated ion channel that has already proven to be useful in the fruit fly [1][2][3][4][5]. The most efficient wavelength for activating ChR2 is 460 nm [6].…”
Section: Introductionmentioning
confidence: 99%